Analysis of Potential New Flood Basin in Ratu Agung Sub-district Using the HVSR Method - Apriana, Yelda; Refrizon; Farid, Muchammad; Onawa, Jonah; Hardianza, Meno; Setyowati, Yuni; Verentina, Sendiya (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Indonesia is a tropical country with high rainfall and diverse topography, making it prone to flooding. In Bengkulu City, the flood risk is particularly high in low-lying and flood basins, which are critical zones for flood risk mitigation. This study aims to analyze the characteristics of rock types and water infiltration potential that may  trigger new flood basins in Ratu Agung District, Bengkulu City. The microtremor method was applied to assess soil  properties based on the dominant frequency (f0), amplification factor (A0), and sediment layer thickness. The analysis showed (f0) values ranging from 1.13 to 8.55 Hz and (A0) values ranging from 0.74 to 4.59. HV-Inv analysis results indicate shear wave velocity Vs values between 53 and 894 m/s, with five sediment layers reaching a depth of 100 m. Higher Vs values generally represent denser, less porous rock, limiting infiltration and increasing surface runoff, which elevates flood potential. The findings of this study are expected to serve as a reference for flood risk mitigation, especially in minimizing infrastructure damage and social impacts in Bengkulu City.